Reciprocity Networks and the Participation Problem - Martin Dufwenberg; Amrish Patel (Center for Economic Studies and ifo Institute (CESifo), 2014)
Reciprocity can be a powerful motivation for human behaviour. Scholars argue that it is relevant in the context of private provision of public goods. We examine whether reciprocity can resolve the associated coordination problem. The interaction of reciprocity with cost-sharing is critical. Neither cost-sharing nor reciprocity in isolation can solve the problem, but together they have that potential. We introduce new network notions of reciprocity relations to better understand this. Our analysis uncovers an intricate web of nuances that demonstrate the attainable yet elusive nature of a unique outcome.
Keywords: C72; D03; H41; 330; discrete public good; participation; reciprocity networks; coordination; cost-sharing